(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the aspects of symbolism origin and its development in the Russian and Kazakh poetry. The outlook of one particular nation is revealed in the process of its cultural and literary connections, spiritual intercommunication with other nations and nationalities. Taking into consideration the Kazakh-Russian literary cultural connections in the last centuries the motives and separate national features uniting them are analysed. Thus this work demonstrates the factors of origin,formation of Russian symbolism at the turn of the centuries and the influence of this trend’s representative A. Blok on the works of the Kazakh poet M. Zhumabayev.In this regard in the article A. Blok’s creativity as the prominent representative of symbolism is considered. A. Blok’s poetry had a great influence on strengthening the creative skills of such Kazakh poets as M. Zhumabayev and B. Kuleev.